Suberites spermatozoon - Morozov, Grigori; Strelkova, Natalya Anisimova; Zimina, Olga; Sabirov, Rushan (Zenodo, 2023)
Suberites spermatozoon (Schmidt 1875) (Fig. 4a–h) Cometella spermatozoon : Schmidt 1875, p. 116; Pl. 1, fig. 2; Thiele 1903, p. 378, fig. 4. Suberites spermatozoon : Fristedt 1885, pp. 18–19; Pl. 2, figs. 4a–e; Fristedt 1887, pp. 429–430. Ficulina spermatozoon : Rezvoi 1928, pp. 82–85, figs. 6–7; Hentschel 1929, pp. 871–872; Burton 1930, p. 496. Suberites lütkenii var. spermatozoon : Arndt1935, p. 41, fig. 65. Choanites spermatozoon : Alander 1942, p.79. Suberites domuncula var. spermatozoon : Koltun 1966, p. 96, fig. 68, Pl. 31, figs. 1–9. Material analyzed. Kara Sea, PINRO trawl survey, Pomor , 1994, st. 3 (72.417N, 59.4378E), depth 157 m (1 specimen). Boris Petrov , 2000, st. 29 (76.9362N, 85.7631E), depth 71 m, temperature -0.3 °C, salinity 34.3 psu (1 specimen); st. 30 (75.9864N, 83.361E), depth 57 m, temperature 0.2 °C, salinity 33.9 psu (2 specimen). Barents Sea, PINRO trawl survey, Muklevich , 2003, st. 34 (72.0385N, 33.3903E)), depth 265 m, temperature 2.66 °C, salinity 34.959 psu (7 specimens, KFU-LH-2/009); st. 35 (72.5178N, 33.5017E)), depth 281.7 m, temperature 1.13 °C, salinity 34.926 psu (9 specimens, KFU-LH-2/010); st. 27 (69.581N, 33.1024E), depth 225.1 m, temperature 3.12 °C, salinity 34.501 psu (1 specimen, KFU-LH-2/011). F. Nansen , 2004, st. 72 (75.0026N, 47.0645E), depth 238.7 m, temperature -0.89 °C, salinity 34.965 psu (1 specimen, KFU-LH-2/012). F. Nansen , 2005, st. 1 (73.5092N, 33.5523E), depth 280.57 m, temperature 0.69 °C, salinity 34.996 psu (3 specimens, KFU-LH-2/013). Description . Sponge pyriform, elongate, more or less laterally compressed, up to 40 mm in length, 5 mm width. The upper parts of the body are rather broad, lobate, sometimes branching, gradually narrowing towards the pedicle (Fig. 4h). Usually there is a single conical osculum on the sponge’s apex. Surface smooth. Consistency is fairly soft, delicate. The color is yellowish (in alcohol). Spicules . Styles (tylo- and subtylostyles) straight, rather short-pointed (sometimes blunt), of one size class only (W = 0.98, p ...